REACTIVE PLASMACYTOSIS AT THE ONSET OF ANGIOIMMUNOBLASTIC T-CELL LYMPHOMA. CASE REPORT - N. G. Chernova; M. N. Sinitsyna; A. M. Kovrigina; Y. V. Sidorova; I. V. Galtseva; S. A. Mar’ina; V. N. Dvirnyk; E. E. Zvonkov (Онкогематология, 2018)
Angioimmunoblastic T-cell lymphoma is a rare T-cell lymphoproliferative disease with generalized lymphadenopathy, hepatosplenomegaly, intoxication and polyclonal hypergammaglobulinemia. The persistence of plasma cells in peripheral blood can be a manifestation of both tumor and reactive processes. In our article, we described the case of angioimmunoblastic T-cell lymphoma with an increase in the number of peripheral blood plasma cells to 28 %, and in bone marrow to 9 %. The complex diagnostics, including plasma cells immunophenotyping, morphology of the lymph node biopsy and bone marrow samples, made it possible to verify the diagnosis of angioimmunoblastic T-cell lymphoma with polyclonal plasmacytosis.